Tổng hợp kháng sinh cefuroxim từ 7-ACA - Tân, Nguyễn Khánh; Nhuận, Đoàn Ngọc (Vietnam Journal of Chemistry, 2016)
Cefuroxime -a second generation cephalosporin antibiotic- is synthesized from starting materials 7-ACA (7-aminocephalosporinic acid) and SMIA (2-furanyl-(Z)-2-methoxyiminoacetic acid ammonium salt). The study showed that the product could be prepared via 4 steps scheme to obtain cefuroxime in good total yield (42 % yield). The novel of the process, that we use oxalyl chloride replaces phosphoryl chloride in step 2: help reaction of step 2 gain yield better. Keywords. 7-ACA, SMIA, decarbamoyl cefuroxime acid, cefuroxime.